2014
DOI: 10.5539/gjhs.v6n4p183
|View full text |Cite
|
Sign up to set email alerts
|

Association between Self-Reported Academic Performance and Risky Sexual Behavior among Ugandan University Students- A Cross Sectional Study

Abstract: Little is known about the association between self-reported academic performance and risky sexual behaviors and if this differs by gender, among university students. Academic performance can create psychological pressure in young students. Poor academic performance might thus potentially contribute to risky sexual behavior among university students. The aim of this study was to investigate the association between self-reported academic performance and risky sexual behaviors, and whether gender affects this rel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
1
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 32 publications
1
8
1
1
Order By: Relevance
“…Based on the findings of this study, students have risky behaviors because they do not use a condom in all sexual relations. In this study, women report a greater use of condoms than men, both in all and in the last sexual intercourse, which contradicts the study of Mehra et al (2014), in which women have a higher prevalence (50%) of inconsistent use of condoms than men (37%; Falcão Júnior et al , 2007). There is also evidence of symmetry between men and women regarding the inconsistent use of condoms (Souza et al, 2011).…”
Section: Resultscontrasting
confidence: 85%
See 2 more Smart Citations
“…Based on the findings of this study, students have risky behaviors because they do not use a condom in all sexual relations. In this study, women report a greater use of condoms than men, both in all and in the last sexual intercourse, which contradicts the study of Mehra et al (2014), in which women have a higher prevalence (50%) of inconsistent use of condoms than men (37%; Falcão Júnior et al , 2007). There is also evidence of symmetry between men and women regarding the inconsistent use of condoms (Souza et al, 2011).…”
Section: Resultscontrasting
confidence: 85%
“…The existence of multiple sexual partners is also a risk factor for STIs. The percentages reach approximately 40% of young people (Mehra et al, 2014;Moghaddam et al, 2015). In this study, 8% of participants reported having between eight and 10 sexual partners.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…(5,15) Reflexos disso são os dados nacionais de 2014 em que se reporta uma diminuição do uso do preservativo e aumento de relações sexuais associadas ao consumo de drogas e álcool, sendo que aqueles que não utilizaram preservativo na 1ª relação sexual apontaram como motivos, em primeiro lugar "não pensaram nisso" (42%) e em segundo o "não tinha preservativos consigo" (31,8%), (5) o que remete nestes jovens para uma iniciação sexual de risco e impregnada de irresponsabilidade, em que está evidente o caráter espontâneo e não planejado dos relacionamentos sexuais entre os jovens, o que leva a que a maioria se inicie sexualmente de uma forma imprevista. (1,5) Apesar de a maioria ter referido a abordagem de conteúdos de sexualidade/contracepção em sala de aulas, (10,14) os estudantes se considerarem bem informados (13) e até referirem a utilização de métodos contraceptivos na primeira relação sexual, (4,10,13) não deixam depois de apresentar comportamentos sexuais de risco significativos, como os verificados no presente estudo pela não utilização sistemática de métodos contraceptivos, (1,4,11) relações sexuais ocasionais (10,16,17) e sob o efeito do consumo de álcool. (5,18) Também um estudo nacional, com grupo de intervenção e avaliação aos 36 meses, demonstrou que alguns resultados importantes, nomeadamente a existência de relações sexuais sob efeito do álcool e não uso de preservativo com parceiro ocasional, não só não melhoraram como sofreram um agravamento.…”
Section: Discussionunclassified
“… Hueng et al (2005) observes that risk behavior increase with age even though knowledge increase with age. Mehra et al (2014) believes that there is an association between poor academic performance and inconsistent condom use with a new sex partner.…”
Section: Introductionmentioning
confidence: 99%